NILAI PERUSAHAAN DIPENGARUHI KEBIJAKAN DEVIDEN DAN KUALITAS LABA (Studi kasus Industri Sub Sektor Otomotif dan Komponennya periode 2016-2019) - Ayu Puspitaningtyas (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to find out how (1) the simultaneous influence devidend policy and earning quality on value of the company of automotive and componens companies, (2) the partial influence of influence devidend policy and earing quality on value of the company of automotive and components companies in the period 2016-2020. This research uses purposive sampling in taking data. The data collected will be analyzed using multiple linear analysis. The result of this research is (1) there is positive significant influence from dividend policy to value of the company, (2) there is negative significant influence from earning quality variable to value of the company, (3) there is a significant effect of dividend policy and earing quality value addedon value of the company simultaneously.